Depression and prognosis following hospital admission because of acute myocardial infarction - Lauzon, Claude (2003)
BACKGROUND: Whether there is an association between depression at the time of acute myocardial infarction and subsequent risk of cardiac complications and death remains controversial. Most studies of this risk factor have been limited to patients of single institutions, and this might account for the varying results. We prospectively evaluated patients admitted to 5 tertiary care and 5 community hospitals and followed them for 1 year to measure the prevalence and prognostic impact of depressive symptoms after acute myocardial infarction. METHODS: Patients were recruited for the study by trained nurse interviewers who had documented acute myocardial infarction within 2–3 days of admission. The nurses collected information from the medical records and asked study subjects to complete the Beck Depression Inventory questionnaire during their stay in hospital and using a mailed questionnaire 30 days, 6 months and 1 year later. We obtained information on vital status for patients lost to follow-up from a central death registry. RESULTS: Of the 587 study subjects, 550 (94%) completed the Beck Depression Inventory at baseline and 191 (35%) had a score of 10 or more, indicating at least mild depression. Rates of depression did not vary over the follow-up period and were similar among patients admitted to tertiary care or community hospitals. Depressed patients were more likely to undergo catheterization (57% v. 47%, 95% confidence interval [CI] around the difference 0.1%–19.6%) and were more likely to undergo percutaneous coronary intervention (32% v. 24%, 95% CI around the difference 0.1%–16.2%) within 30 days of first admission to hospital. Patients with depression on admission had higher rates of a composite of cardiac complications, including recurrent ischemia, infarction or congestive heart failure during their first stay in hospital or readmission for angina, recurrent acute myocardial infarction, congestive heart failure or arrhythmia (adjusted hazard ratio 1.4, 95% CI 1.05–1.86), compared with patients who were not depressed on admission. After 1 year, death rates were higher among patients who were depressed at admission (30 patients, 16%) compared with nondepressed patients (28 patients, 8%), although the difference was not statistically significant (hazard ratio 1.3, 95% CI 0.59–3.05). INTERPRETATION: Depressive symptoms are common after acute myocardial infarction and are associated with a slight increase in risk of in-hospital catheterization and angiography and readmission because of cardiac complications. Death was infrequent, with no statistically significant difference between the 2 groups.